DISTRIBUTION OF LEMONGRASS OIL (CYMBOPOGON NARDUS L) USING SUN RAYS BY USING SOLAR CELL (PHOTOVOLTAIC) - Muhammad Jazuli; Teuku Rihayat; Muhammad Rezi Syahputra; Shafira Riskina (Politeknik Negeri Lhokseumawe, 2017)
In the use of solar light, many things can be applied with electrical energy produced using solar cells. With the use of solar cells that are used as many as 4 units of solar cells with a capacity of 1000 wp, so in a day able to produce electrical energy as much as 28,000 watts. This is a very potential electrical energy because it is commonly used to facilitate the process of refining essential oils. The results and the quality of the oil obtained in refining research using electrical energy by utilizing sunlight using solar cells shows that the refining time of 6 hours is the best time for the refining process, while the 1 day drying time is better than 2 and 3 days. This is consistent with the oil yield obtained. As for the results of the Fragrant Lemongrass, Laboratory Test produced already meet the Indonesian quality standard, where the value of the density test, Bias Index, Uv-Vis and GC-MS are in the range of the Indonesian National Standard (SNI) 2385-2006.